Development of an improved thermal model of the human body and an experimental investigation of heat transfer from a moving cylinder - Sun, Xiaoyang (Kansas State University, 2011)
A new human thermal model was developed to predict the thermal responses of human body in various environments. The new model was based on Smith's model, which employed finite element method to discretize the human body. The body parts in our new model were not limited to the cylindrical shape as in Smith's model, but subjected to arbitrary shapes. Therefore, the new model is capable of dealing with more complicated shapes of the human body. Steady-state and transient temperatures of fifteen body parts were calculated for three environments: cold, neutral, and warm. Our results were compared with the data from Zhang's experimental research on the human subjects. For all three conditions, our results showed better agreement with experimental data than Smith's results did. The maximal deviation is 1ºC for neutral and warm condition; for cold condition, a maximal deviation of 3.5ºC is reported at hand. The comparison indicated that our new model could provide a more accurate prediction on the body temperatures. Follow-up experiments were conducted to investigate the local and overall heat transfer from a moving cylinder in air flow. This study was expected to provide the local convective heat transfer coefficients of the human body to our new human thermal model to simulate moving humans. An experiment of a stationary cylinder in cross flow was performed to verify the accuracy and consistency of our system. Then, the experiment of a transverse oscillating cylinder in cross flow was conducted, with a oscillation frequency of 0.15 and Strouhal number of 0.3 to 1.5, depending on wind velocity. The overall Nusselt number (Nu) of the oscillating cylinder remained unaffected, compared to the stationary cylinder. This observation showed agreement with previous studies. The pivot experiment was performed to investigate swinging movement of human arms. The cylinder was positioned axially in cross flow, and reciprocated on a fixed point between horizontal and vertical positions under three wind speeds and two oscillating frequencies. The results showed that the overall Nu was between the Nu at horizontal and vertical positions in stationary state. A correlation was presented to predict the Nu of pivotal moving cylinder by using stationary Nu at horizontal and vertical positions. The correlation was proved to be valid ( error less than 5%) within the range of conditions in our experiment.
Keywords: Thermal model; Simulation; Moving cylinder; Heat transfer coefficient; Engineering (0537); Environmental Engineering (0775); Mechanical Engineering (0548)